2020
DOI: 10.1186/s12890-020-01336-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum SP-A and KL-6 levels can predict the improvement and deterioration of patients with interstitial pneumonia with autoimmune features

Abstract: Background Some patients with interstitial pneumonia with autoimmune features (IPAF) showed a progressive course despite therapy. This study aimed to evaluate whether serial changes in the serum levels of surfactant protein-A (SP-A) and Krebs von den Lungen-6 (KL-6) can predict disease progression. Methods Sixty-four patients with IPAF and 41 patients with non-fibrotic lung disease (non-FLD) were examined. Based on long-term changes in lung functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
18
0
3
Order By: Relevance
“…(Mild ILD: n = 335, Severe ILD: n = 223). Mean (SD) concentrations of KL-6 for patients in progressive ILD and non-progressive ILD groups were collected from 12 studies ( 11 , 18 , 25 , 28 , 29 , 31 , 35 , 36 , 38 , 45 , 47 , 53 ). (Progressive ILD: n = 203, Non-progressive ILD: n = 511).…”
Section: Resultsmentioning
confidence: 99%
“…(Mild ILD: n = 335, Severe ILD: n = 223). Mean (SD) concentrations of KL-6 for patients in progressive ILD and non-progressive ILD groups were collected from 12 studies ( 11 , 18 , 25 , 28 , 29 , 31 , 35 , 36 , 38 , 45 , 47 , 53 ). (Progressive ILD: n = 203, Non-progressive ILD: n = 511).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, higher levels of SP-A and KL-6 predicted severe decline in pulmonary function. 154 In addition, Kameda and colleagues 155 demonstrated that serum and BAL levels of CXCL9, CXCL10 and CXCL11 were significantly increased in patients with IPAF and CTD-ILD compared to IPF. Further studies are needed to validate the clinical significance of these novel biomarkers before becoming part of routine clinical assessment of patients with IPAF.…”
Section: Interstitial Pneumonia With Autoimmune Features (Ipaf)mentioning
confidence: 99%
“…KL-6 levels were significantly higher in the patients with IPAF than in the patients with non-IPF interstitial fibrosis, non-fibrotic lung diseases, pneumonia and a healthy group [ 18 , 19 , 20 , 22 ]. The biomarker level, when compared to IPF, was varied depending on the study: it was significantly higher in IPAF in Kameda’s study, but comparable in Xue’s study [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in three studies, the serum KL-6 levels showed a negative correlation with the transfer factor for carbon monoxide (T LCO ) [ 19 , 20 , 22 ]. The results of the studies regarding the correlation between KL-6 and the percentage of predicted forced vital capacity value (%FVC) differed from study to study: there was no significant correlation with %FVC and the percentage of predicted forced expiratory volume in one second value (%FEV 1 ) in Wang’s publication, whilst the association with %FVC was described in Xue’s article [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%